A match coefficient approach for damage imaging in structural components by ultrasonic synthetic aperture focus. (2017) - Sternini, S.; Quattrocchi, A.; Montanini, R.; Pau, A.; di Scalea, F. Lanza
Abstract: Ultrasonic Synthetic Aperture Focus (SAF) techniques are commonly used to image structural defects. In this paper, a variation of SAF based on ideas borrowed from Matched Field Processing (MFP) is evaluated to reduce artifacts and sidelobes of the resulting images. In particular, instead of considering the full RF ultrasonic waveforms for the SAF time backpropagation, only selected features from the waveforms are utilized to form a "data vector" and a "replica" (expected) vector of MFP. These vectors are adaptive for the pair of transmitter-receiver and the focus point. The image is created as a matched filter between these two vectors. Experimental results are shown for an isotropic and homogenous metallic plate with simulated defects, probed by six piezoelectric patches used as receivers or transmitters.